2006
DOI: 10.1203/01.pdr.0000220322.31940.29
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii Produces in Rat Small Intestine a Novel Protein Phosphatase that Inhibits Escherichia coli Endotoxin by Dephosphorylation

Abstract: Using a polyclonal antibody raised against a highly conserved sequence of 38 amino acids containing the activation site (VTDSAAGAT) common to mammalian and yeast alkaline phosphatases (AP), we identified in decapsidated Saccharomyces boulardii a protein phosphatase detected by autoradiography as a single signal (63 kD). Using an affinity chromatography column, the protein phosphatase could be concentrated 39.1-fold and presented as a doublet of two subunits. Compared with rat and bovine purified intestinal AP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 19 publications
1
73
1
4
Order By: Relevance
“…One study in an animal model identified in Sb a protein phosphatase that had a greater ability to dephosphorylate LPS of E. coli, which when injected in rats produced substantially less TNF-␣ and no organic lesions compared with the non-Sb-exposed LPS (11,12). However, this observation would not explain the other novel immunological and epithelial restitution effects demonstrated by us.…”
Section: Discussionmentioning
confidence: 64%
“…One study in an animal model identified in Sb a protein phosphatase that had a greater ability to dephosphorylate LPS of E. coli, which when injected in rats produced substantially less TNF-␣ and no organic lesions compared with the non-Sb-exposed LPS (11,12). However, this observation would not explain the other novel immunological and epithelial restitution effects demonstrated by us.…”
Section: Discussionmentioning
confidence: 64%
“…Luminal action A) Antimicrobial activity 1) Inhibition of growth of bacteria and parasites Czerucka et al 1994;Czerucka and Rampal, 2002;Dahan et al 2003;Dalmasso et al 2006a;Gedek, 1999a;Rigothier et al 1994;Rodrigues et al 1996;Mumy et al 2008;Wu et al 2008] 2) Reduction of gut translocation of pathogens [Herek et al 2004;Geyik et al 2006] 3) Neutralization of bacterial virulence factors [Buts et al 1994;Jahn et al 1996] 4) Suppression of host cell adherence that interferes with bacterial colonization [Czerucka et al 2000;Rodrigues et al 1996;Wu et al 2008] B) Antitoxin effects 1) Inhibition of toxin receptor binding sites [Buts et al 2006;Castagliuolo et al 1996Castagliuolo et al , 1999Czerucka et al 2000;Tasteyre et al 2002;Wu et al 2008] 2) Stimulation of antibody production against Clostridium difficile toxin A [Brandao et al 1998;Qamar et al 2001] 3) Direct proteolysis of the pathogenic toxins/Secretion of enzymatic proteins [Buts et al 2006;Castagliuolo et al 1996;Pothoulakis et al 1993] a) Produces a serine protease that cleaves C. difficile toxin A [Pothoulakis et al 1993] b) Produces 63 kDa phosphatase that destroys the endotoxin of pathogenic Escherichia coli [Buts et al 2006;Castagliuolo et al 1996] c) Produces a 120 kDa protein that reduces the effects of cholera toxin [Czerucka et al 1994] C) Cross-talk with normal microbiota When S. boulardii is given to antibiotic-exposed mice or patients with diarrhea, normal microbiota is re-established rapidly [Buts et al 1986[Buts et al , 1999[Buts et al , 2006Buts, 2009;…”
Section: Action Of Saccharomyces Boulardii Referencesmentioning
confidence: 99%
“…Clostridium difficile infection 1) Inhibits toxin A-mediated diarrhea, intestinal inflammation and histological damage by reducing toxin A-receptor binding [Castagliuolo et al 1996;Pothoulakis et al 1993] 2) Releases a protease that cleaves C. difficile toxins and toxin intestinal receptors [Castagliuolo et al 1996;Pothoulakis et al 1993] 3) Stimulates specific intestinal antitoxin A immunoglobulin levels [Castagliuolo et al 1996[Castagliuolo et al , 1999Pothoulakis et al 1993] 4) Inhibits IL-8 production and activation of the MAP kinases Erk1/2 and JNK/SAPK induced by C. difficile toxin A in human colonocytes Qamar et al 2001] 5) Significantly fewer animals challenged with C. difficile died if given S. boulardii compared with controls [Castex et al 1990;Elmer and Corthier, 1991;Rodrigues et al 1996;Toothaker and Elmer, 1984] Helicobacter pylori infection Alters the structure of H. pylori Vibrio cholerae infection 1) Inhibits the effect of V. cholerae toxin and hydroelectrolytic secretions by reducing cAMP activity [Vidon et al 1986;Czerucka et al 1994] 2) S. boulardii and the mammalian CT receptors could be structurally and functionally similar and the yeast binds CT [Brandao et al 1998;Czerucka et al 1994] Amebic dysentery 1) Reduces the number of red cells adhering to amoebae [Rigothier et al 1994] 2) Decreases the number of amoebae bearing red cells [Rigothier et al 1994] Infection with EHEC 1) S. boulardii modifies host signaling such as NF-κB-associated pathways activated by bacterial invasion with EHEC [Dahan et al 2002[Dahan et al , 2003 2) Addition to T84 colonocyte monolayers diminishes MLC phosphorylation and decreases transepithelial resistance in response to EHEC [Dahan et al 2002[Dahan et al , 2003 Infection with EPEC 1) Modifies EPEC infection and acts as a receptor decoy for EPEC [Buts et al 2006;Canil et al 1993;Czerucka et al 2000;Gedek, 1999b] 2) Reduces the number of intracellular EPEC [Buts et al 2006;Canil et al 1993;Czerucka et al 2000;Gedek, 1999b] 3...…”
Section: Action Of Saccharomyces Boulardii Referencesmentioning
confidence: 99%
“…It has been shown that S. boulardii has the capacity to release factors which neutralize bacterial toxins and decrease the deleterious effects of infectious pathogens (Buts et al, 2006;Castagliuolo et al, 1996;Castagliuolo et al, 1999). C. difficile is responsible of AAD in humans and animals, and is one of the most common nosocomial pathogens.…”
Section: Neutralization Of Bacterial Toxinsmentioning
confidence: 99%
“…S. boulardii produces also a 63 kDa protein phosphatase that inhibits the LPS toxicity of enteropathogenic E. coli O55B5 by endotoxin dephosphorylation (Buts et al, 2006) ( Figure 2C). Intraperitoneal injection of dephosphorylated LPS in rats decreases the level of circulating TNF-α and abolishes inflammatory lesions in comparison to rats injected with native LPS.…”
Section: Neutralization Of Bacterial Toxinsmentioning
confidence: 99%